Attitudes of nursing students toward to the suicidal behavior - Kelly Graziani Giacchero Vedana; Ana Carolina Guidorizzi Zanetti (Universidade de São Paulo, 2019)
ABSTRACT Objective: to investigate attitudes related to suicidal behavior and associated factors, among students in the last year of an undergraduate nursing course. Methods: a cross-sectional study with 111 nursing students from a Brazilian educational institution. The data were collected in 2017, by self-administration of a questionnaire with sociodemographic characteristics, and the Suicide Behavior Attitude Questionnaire, which were analyzed by descriptive statistics, comparison of means, and correlation tests. Results: most of the nursing students had contact with someone with suicidal behavior, but did not have education related to the subject. The most negative attitudes were associated with the female sex, lack of materials on suicide prevention, and lower self-perception of professional competence. Suicidal thoughts throughout life were associated with the contact with someone with suicidal behavior, and less moralistic/condemnatory attitudes. Conclusion: investigations and interventions are necessary for academic qualification and prevention of suicidal behavior.